Expression of Estradiol-17β (ERβ) Receptor Protein in Whole Cortical Slices of Sheep Ovary - B, Supriya; Kumar, A V N Siva; Jamuna, K V; P, Deepa; Ramayya, P Jagapthi (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Estradiol 17β receptor (ERβ) protein expression in various cells of sheep ovaries was studied through immunohistochemistry. The ovaries recovered from eight adults apparently healthy sheep immediately after their slaughters were studied in the embryo biotechnology laboratory of Sri Venkateswara Veterinary University, Tirupati. The surface epithelial cells covering the ovary showed moderate immunoreactivity. The ovum of primordial follicles showed intense reaction and that of primary and secondary follicles showed moderate reaction. In early antral follicles, both ovum and granulosa cells showed moderate immunoreactivity. The theca cells were not immunoreactive. In antral follicles ovum and granulosa cells showed strong reactivity and theca interna cells showed mild to moderate reactivity. The cells of the corpus luteum showed moderate cytoplasmic immunoreactivity.